Physiotherapy Management of Post Operating Achilles Tendon Ruptural (Phase III): A Case Study - Khadijah, Siti; Maulana, Hakny; Agustyaningsih, Nur Afni; Salsabila, Dika Tiara; Annisa, Nur (Academic Physiotherapy Conference Proceeding, 2023)
Introduction: Physical injuries can disrupt the musculoskeletal system which includes muscles, bones, joints, tendons, ligaments, and the connective tissue that supports and binds tissues and organs together. The incidence of achilles tendon rupture has increased due to increased physical activity and sports, especially at the age of 30 and 40 years. Physiotherapy is a form of health service aimed at individuals and/or groups to develop, maintain and restore body movement and function throughout the life span by using manual handling, increased movement, equipment (physics, electrotherapeutic and mechanical), function training, and communication. Case Presentation: The patient was diagnosed with Achilles tendon rupture. The course of the disease was that the patient was playing mini soccer, when the patient ran sprints then his left foot stepped on it and a clicking sound was heard, after the injury the patient was still forced to walk, starting from there the patient felt quite disturbing pain, followed by edema in the left ankle and loss of joint stability. The physiotherapist performed a static inspection with the result that there was an incision along the left Achilles tendon, the patient's postural condition was good, there was visible edema of the left lateral malleolus. The results of a dynamic inspection check are that it can be seen that the running time is still based on the right side of the axle. Management and Outcome: The physiotherapy modality used is to provide cold compresses for 5 minutes. Before being given an exercise program, do a warm-up first. Then proceed with a static cycle for 15 minutes, closed chain exercise, lunges (3 sets), squad (3 sets), calf rises (3 sets), balance exercise, the single-leg brige (3 sets). When finished proceed with cool down. The results of this study were a decrease in edema which was evaluated by a figure of eight, but there was no change in muscle strength which was evaluated by MMT and functional ability which was evaluated by the FADI scale. Discussion: A decrease in edema can occur due to the icing modality or it can also be called a cold compress. Cryotherapy can show a decrease in edema, because cryotherapy can cause cold stimulation to skin tissue which can cause local vasoconstriction causing a decrease in edema fluid and lymph fluid production which can release inflammatory mediators through decreasing the permeability of blood vessel walls resulting in decreased edema. Close Chain Kinetic exercises provide activation of antagonistic groups of several joint group. Examples of closed chain exercises include pushups, pullups, squats, and lunges. All types of closed chain exercises can be performed whether using weights or not. Kinetic Closed Chain training focuses on eccentric muscle work, as it is known that eccentric training can develop higher muscle contractions in the muscles so that a greater training effect can be obtained and followed by increased functional performance. Conclusion: Management of physiotherapy programs given for 2 times resulted in the results that the initial therapy to the final therapy had not shown significant results. So it can be concluded that the left ankle edema has decreased, there is still muscle weakness, and there is no change in the patient's functional ability.